Comparative Qualitative And Antibacterial Study Of Bixa Orellana L. Leaves With Some Selected Solvent For Some Selected Bacteria (International Journal of Food and Nutritional Sciences, 2022)
A quantitative assessment of antimicrobial activities was carried out by determining theminimum inhibitory and microbicidal concentrations (MICs and MMCs) of the various solventextracts like 70% ethanol, water , ethyl acetate and chloroform against two Gram negativebacteria - Escherichia coli and Pseudomonas aeruginosa and two Gram positive bacteria -Staphylococcus aureus and Bacillus cereus,. The testing was done by the Agar disc diffusionmethod. Zones of inhibition of extracts were compared with that of standard ofloxin andamoxicillin antibiotics for antibacterial activity. From our study, we can conclude that ethanolextract has more prevailing and sustainable antibiotic properties than other solvents extract.Preliminary phytochemical screening of Bixa Orellana showed the presence of alkaloids,glycosides, steroids, phenols, tannins, flavonoids and saponins in the crude drug.